Impact loading on body segments as a function of running speed - Nagano, A.; Fujimoto, M.; Otsuka, M.; Isaka, T. (International Calgary Running Symposium, August 14-17, 2014, 2014)
Impact loading during running is an important factor associated with running injuries. The objectives of this study were (1) to evaluate impact loading on the foot, lower leg, upper leg, pelvis, spine, and head during running, (2) to investigate the relationship between the impact load and the running speed, and (3) to assess the variability of impact loading pattern while running for a long period of time (10-20 minutes). Ground reaction forces (GRFs) acting on each leg while running at a constant speed were collected using an instrumented split-belt treadmill which can measure three force and three moment components for each leg (Tec Gihan, Co., Ltd., Japan). The running speed was systematically adjusted for slow jogging to fast running conditions. Three acceleration and three angular velocity components of body segments were measured using wireless wearable inertia sensors (ATR-Promotions, Inc., Japan). We attached the sensors to each foot, lower leg, upper leg, pelvis, spine, and head segment. The data, combined with the GRFs, were used to estimate the impact load on each segment. We found that the sharp impact at the heel contact was attenuated in segments further towards the head. The magnitude of attenuation changed as a function of running speed. The variability of impact profile also changed as a function of running speed. These findings would be useful in the design of effective training programs while avoiding running injuries.